2015
DOI: 10.1016/j.biopha.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aberrantly expressed of serum microRNAs in patients with hormone-induced non-traumatic osteonecrosis of the femoral head

Abstract: We report a miRNA profile of hormone-NOFH and provide a new perspective to understand this intricate disease. This novel information suggests the potential roles of miR-423-5p in the diagnosis, prognosis biomarkers, or therapy targets of hormone-NOFH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…Wei et al suggested that miR-596 exerted the role in glioma invasion via regulating CREPT [46]. In patients with SANFH, miR microarray analysis showed that miR-596 level in plasma was significantly elevated [18]. However, the function of miR-596 in SANFH remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wei et al suggested that miR-596 exerted the role in glioma invasion via regulating CREPT [46]. In patients with SANFH, miR microarray analysis showed that miR-596 level in plasma was significantly elevated [18]. However, the function of miR-596 in SANFH remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-596 is a kind of miRNAs, which was indispensable for the differentiation, proliferation, and migration of cancer cells [16,17]. It was reported that plasma miR-596 level was significantly increased in patients with NOFH, which had potential diagnostic value for NOFH [18]. However, the underlying mechanisms of miR-596 in SANFH are unclear.…”
mentioning
confidence: 99%
“…miR-423-5p is downregulated in osteosarcoma cells expressing CD117 and STRO-1 (21). The miR-423-5p levels were considerably elevated and correlated with the prognosis of patients with hormone-induced non-traumatic osteonecrosis of the femoral head (27). These studies indicate that miR-148b-3p, miR-337-5p and miR-423-5p participate in osteoclast metabolism.…”
Section: Discussionmentioning
confidence: 70%
“…ey further revealed that the regulatory effect of miR-1207-5p on steroid-induced ONFH was related to its effect on epidermal growth factor receptors using rat models. [23] used a miRNA microarray to profile miRNA expression in the serum of patients with steroid-induced ONFH and healthy volunteers in an attempt to identify new biomarkers for diagnosis. ey found three miRNAs that were downregulated and nine miRNAs that were upregulated in the serum of the ONFH patients.…”
Section: Micrornas In Steroid-induced Onfhmentioning
confidence: 99%